Why Europe should embrace Turkey - Barysch, Katinka; Everts, Steven; Grabbe, Heather 1970- (Centre for European Reform, 2005)
Grabbe, H.: From drift to strategy : the case for Turkey's accession. - S. 11-22 Barysch, K.: The economics of Turkish accession. - S. 23-42 Grant, C.: Bon on Turkey and EU foreign policy. - S. 43-46 Everts, S.: An asset but not a model : Turkey, the EU and the wider Middle East. - S. 47-68 Grabbe, H.: When negotiations begin : the next phase in EU-Turkey relations. - S. 69-82